The Cruelty of the Curative - Veitch, Alanna; Rinaldi, Jen (Atlantis, 2026)
In this paper, we take up Lauren Berlant’s (2011) theoretical framing of cruel optimism to ground our critique of normalizing scripts around disability, recovery, and healing which shape conceptualizations of health. We argue that these scripts do little to account for the multitude of disability experiences that meet and cycle through intersections of race, gender, class, culture, sexuality, and personhood. This work first requires engaging with mainstream perspectives on recovery and healing which undergird Western rehabilitative practices, and a turn toward Black and Indigenous conceptualizations of health and healing as practices grounded in community and social justice. We situate our review and discussion within a North American and Canadian context. Next, we describe the arts-informed counter-narrative methodology we utilize to share glimpses into our digitized disability stories. Our stories comprise moments of disruption, vulnerability, and isolation, enabling us to transform silence into language and action, and to reflect on the intricate dance between disability, health, and illness we are bound up in and continue cycling through. We show how our counter-narratives, when brought together, challenge the “getting better” meta-narrative. We target notions of getting better because, like the cruel promise of recovery, they idealize a return to “normal” and dismiss histories that bear on the present in felt and embodied ways. Rather than “getting better,” bound up in fantastical promises, we find the authenticity of our own failures and vulnerabilities generative, indecipherable, and enduring.